Unveiling strategies in acute cardiac care for ventricular septal rupture following acute myocardial infarction: Lessons from cases - Nurudinulloh, Akhmad Isna; Anjarwani, Setyasih; Prasetya, Indra; Yogibuana, Valerinna; Rahimah, Anna Fuji; Karolina, Wella (Heart Science Journal, 2025)
Background: Ventricular septal rupture (VSR) following acute myocardial infarction (AMI) is drastically decreasing in the reperfusion era but mortality remains high. VSR correction is the definitive treatment and using mechanical support to delay closure is an attractive option despite data on success being limited. Case Illustration: A 60-year-old man presented with late presentation of anterior STEMI complicating hemodynamic deterioration. Echocardiography showed apical VSR 11-14 mm L-R shunt. Patient was given adequate fluids, multiple inotropic agents, and IABP insertion, then a successful PPCI procedure was performed immediately. IABP was maintained for hemodynamic stabilization and patient was scheduled for interventional closure. Unfortunately, the patient worsened due to cardiogenic shock and passed away on the 5th day of admission. In another case, a 61-year-old man came to our hospital also with a late presentation of anterior STEMI but stable in hemodynamics. Echocardiography showed apical VSR 9-11 mm L-R shunt. Coronary angiography showed CAD three vessel disease with critical stenosis at LAD. In hospital’s heart team discussion, patient was planned to be performed VSR closure percutaneously and continue with PCI procedure. Both procedures were performed successfully. Patient was improved and discharged on 20th day of admission. Conclusion: Rapid diagnosis and prompt treatment are the keys to optimal management of VSR complicating late presentation STEMI. Mechanical circulatory support and correction of VSR are required to optimize patient outcomes despite VSR is still a challenging case.